Implementasi Kebijakan Praktek Kerja Lapangan (PKL) terhadap Kesiapan Kerja Siswa di SMK Negeri 7 Bone - Sarmila Sarmila; Abd. Moris; Saril Saril (JURNAL MAPPESONA, 2025)
This study analyzes the implementation of the Internship Program (Praktik Kerja Lapangan/PKL) at SMK Negeri 7 Bone and its contribution to developing students’ work character and job readiness, highlighting the importance of integrating education and industry in vocational education. Using a qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis involving school leaders, vocational teachers, and industry partners. The findings reveal five main themes: collaborative and structured planning, implementation based on synchronized learning outcomes and industry curriculum, active mentoring and supervision, continuous monitoring and evaluation with constructive feedback, and the positive impact of PKL on students’ work ethic, soft skills, and employability. The study shows that the partnership between the school and industry is not merely formal but institutionalized through official MoUs, intensive communication, and tangible employment opportunities for students. In conclusion, a systematically managed PKL effectively bridges the gap between theory and practice, strengthens the link and match policy in vocational education, and underscores the role of local actors in policy implementation. The results have theoretical implications for reinforcing actor-based approaches, practical implications for improving PKL management and mentoring systems, and policy implications for promoting adaptive, participatory, and outcome-oriented vocational education. Future studies are recommended to explore the long-term impact of PKL on students’ transition to the labor market and to compare different PKL models across vocational schools.